RISK-DRIVEN PROFITABILITY IN INDONESIAN LISTED BANKS: CAPITAL, LIQUIDITY, AND CREDIT ROLE - Fatimah Ladiza Nuradhelia Anugrah; Maria C. Widiastuti (Program Studi Akuntansi Institut Teknologi dan Bisnis Asia Malang, 2026)
Objective of this study is to investigate the key factors influencing bank profitability. The research utilizes a group of banks listed on the Indonesia Stock Exchange within a defined observation timeframe. employing panel data analysis methods for data processing. According to Ma’aji et al. (2025) The results indicate that various internal bank factors have differing effects on profitability. This study underscores the significance of effective financial management in making sure of the stability and profitability of banking institutions. It aims to evaluate the influence of key determinants, including bank capital, credit risk, liquidity risk, bank size, loan growth, and operational efficiency, on bank profitability. The analysis is based on a sample of banks listed on the Indonesia Stock Exchange over the 2020–2024 period, utilizing a panel data regression model. The empirical findings demonstrate that bank capital exerts a positive and statistically significant effect on profitability, indicating that a stronger capital base enhances a bank’s capacity to generate returns. Conversely, efficiency is observed to have a significant negative impact, implying that higher levels of inefficiency adversely affect financial performance. Meanwhile, credit risk, liquidity risk, bank size, and loan growth do not exhibit a statistically significant relationship with bank profitability.